STRATEGI PENINGKATAN KUALITAS PRODUK DALAM RANTAI PASOK KOMODITI PISANG DI PROVINSI BENGKULU - Odi Andanu; Faqih Udin; Titi Candra Sunarti (Jurnal Teknologi Industri Pertanian, 2021)
A well-being supply chain system will affect on the sustainability of the production and consumer’s satisfaction. Consumer’s need will be fulfilled if the served quality is in the accordance with consumer’s expectations. This study aimed to identify banana supply chains, determine product quality attributes, and strategies for improving the quality of banana products. The methods used were Van der Vorst supply chain management framework, Quality Function Deployment (QFD), and Analytical Hierarchy Process (AHP). The research results exposed that banana supply chain consisted farmers, traders, industries, retailers, and consumers. The dominant quality factors on thise supply chain were the harvest planning (0.24) and harvesting technique (0.19) for fresh bananas; the frying (0.28) and the packaging (0.20) for sale banana; the frying (0.28) and the packaging (0.17) for banana chips. Meanwhile, the quality attributes for fresh bananas were fruit maturity and damage level, for sale bananas were taste and texture, and for banana chips were taste and level of cracked chips. The proposed strategies to improve product quality in the banana comodity supply chain were an increase ability or skill in the production process for each actor (0.25), using standards in the product production process (0.22), make a explicit contractual agreements between actors regarding product quality (0.21), establish a structur farmer group institutions (0.13), optimizing local wisdom (0.10) and the government’s role in assisting farmer and industrial development (0.08). Keywords: banana products,quality improvement, supply chain